Penguatan Kapasitas Pengelolaan UMKM melalui Pendampingan dan Pengembangan Paguyuban di Desa Jambangan, Kecamatan Dampit, Kabupaten Malang - Hindiawati, Wahyu; Kirom, Novita Rifaul; Refangga, Galih Setyo (Abdimas Indonesian Journal, 2025)
This community service program aims to: 1) provide socialization to Jambangan Village MSME partners related to the management and development of Jambangan Village MSMEs through the MSME Association; 2) Providing assistance in terms of managing legality both related to the newly formed Jambangan Village MSME Association and assistance to MSME actors related to the business that has been run. The methods or steps carried out in this community service include: 1) socialization of activities between the service team and MSME Partners; 2) Assistance in the management of business licenses; 3) Assistance in the preparation of Partner Cooperation Letters; 4) Intense production assistance; 5) Application of Technology. The application of technology is carried out by holding training and assistance related to inventory management, packaging and delivery of goods, as well as optimizing the marketing strategy of MSME products through the E-Commerce platform; 6) Evaluation of service activities; Evaluation activities are carried out regularly, namely monthly evaluation, quarterly evaluation and final evaluation; 7) Program Sustainability. Community service activities for MSMEs will be carried out continuously or continuously, including the following: a) consistency of evaluation and improvement (monitoring); b) Medium-term strategic planning. This program is expected to improve the business capabilities of MSME actors individually and collectively, build a competitive, collaborative, and sustainable MSME ecosystem, encourage the formation of independent MSME associations and be able to become long-term partners in village economic developmen.